Simultaneous Kinetic-Spectrophotometric Determination of Levodopa and Carbidopa - KARIMI, M.A.; MAZLOUM ARDAKANI, M.; AMIRYAN, H. (Asian Journal of Chemistry, 2010)
Simultaneous kinetic-spectrophotometric determination of binary mixture of levodopa and carbidopa by principal component regression (PCR) and partial least squares (PLS) calibration is described. The methods were based on the difference in the reduction rate of Fe(III) with levodopa and carbidopa in the presence of 2,2'-bipyridine (Bpy). The coloured complex of [Fe(Bpy)3]2+ resulted can be monitored at 520 nm. The results show that using PCR and PLS, levodopa and carbidopa can be determined simultaneously in the concentration ranges of 0.04-6.0 and 0.05-5.0 μg mL-1, respectively. The root mean squares errors of prediction (RMSEP) of levodopa and carbidopa were 0.0161 and 0.0191 (for PLS), 0.0632 and 0.1313 (for PCR), respectively. Both the methods (PCR and PLS) were validated using a set of synthetic sample mixtures for simultaneous determination of levodopa and carbidopa in pharmaceutical preparation. The recoveries were satisfactory and statistically comparable to those obtained by the reference method of high performance liquid chromatography.